Phototransformations of non-toxic antioxidants, the derivatives of 1,2-dihydroquinolines, in homogeneous and micellar solutions - T. D. Nekipelova (International Journal of Photoenergy)
Reactions of transient species photogenerated from 6-R-2,2,4-trimethyl-1,2-dihydroquinolines (TMDQ) are very sensitive to medium variation. In anhydrous organic solvents, aminyl radicals were generated. They decay in the reaction of dimerization with the second-order rate constant decreasing in a row heptane>benzene>2-propanol. When passing from organic solvents to water, methanol, and water-alcohol solutions, the kinetics and the direction of the reaction crucially change. As a result of the photolysis, the product of the addition of a solvent to the double bond of heterocycle, 4-hydroxy- or 4-methoxy-6-R-2,2,4- tetramethyl-1,2,3,4-tetrahydroquinoline is formed in water and methanol, respectively. The transformation is a complex reaction, and the formation of excited transient species is followed by a sequence of first-order and pseudo-first-order reactions. Unlike the photolysis in anhydrous organic solvents, the reaction in water and methanol does not involve aminyl radicals. In aqueous solutions, the first-order rate constants for the decay of transient species are higher in acidic and neutral solutions. At the pH close to pKa of the transient species, it drops, indicating that the neutral form is less reactive. The same product is formed over the whole range of pH. For the anionic surfactant (SDS) in acidic and alkaline solutions, the apparent rate constant in the micellar solutions is lower than that in the aqueous (negative micellar catalysis). At the medium pH, a positive micellar catalysis is observed, and the rate constant of the decay depends linearly on the concentration of TMDQ in the micelles, indicative of the direct reaction between TMDQ and the cationic transient species.